Pengaruh Fraud Diamond Terhadap Kecurangan Laporan Keuangan - Adela Wilantari; Nanu Hasanuh; Sri Suartini; Hari Sulistiyo (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The aim of this research conducted to examine whether there is a partial or simultaneous influence of the fraud diamond theory, as proxied by financial target, ineffective monitoring, audit opinion, and change in director on fraudulent financial reporting of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2020, the measurement of which is by using the fraud score model (F-Score). Purposive sampling method was used in this study, with sample criteria including manufacturers listed on the Indonesia Stock Exchange (IDX) in 2019-2020, companies that publish their annual reports on the IDX website, companies that presented financial reports in Rupiah, and companies that fully disclose data related to research variables. A sample of 15 companies was obtained based on these parameters. This research was conducted by the quantitative method, and the analysis strategy was multiple regression analysis with an SPSS testing device. According to the results, financial target and ineffective monitoring variables had a partial influence on fraudulent financial reporting, while audit opinion and changes in director had no partial effect. The results also showed that the four independent variables, namely financial targets, ineffective monitoring, audit opinion, and change of director had a simultaneous influence on fraudulent financial reporting.